The Role of Generative Artificial Intelligence in Strategic Decision Evaluation: Analysis of Consistency and Bias in Business Decision Making - Shinta Amelia; Grace Yulianti (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This study aims to review the use of generative artificial intelligence (AI) in strategic decision evaluation, with a focus on consistency and bias in business decision making. Through a qualitative literature review approach, this study analyzes various studies that examine how AI technology, such as the GPT model, can improve decision quality by providing more objective and consistent data analysis. Although it has great potential in reducing human bias, this study also shows the risk of algorithmic and data bias that can affect decision outcomes. Therefore, the use of AI in decision making must be accompanied by strict human supervision to ensure the quality and fairness of the resulting decisions. The results of this study provide an important contribution to the understanding of the challenges and opportunities of AI in strategic decision making in the business world.